Atypical Presentation of Lymphomatoid Granulomatosis in a Patient with Longstanding Sarcoidosis - Paul S Koh; Annette HC Foyle; Yannick Cartier; G Ross Langley; Nancy J Morrison; Graeme Rocker; Alan G Casson (Canadian Respiratory Journal)
A patient was recently evaluated who had longstanding sarcoidosis with lymphadenopathy and multiple, small lung nodules, and who developed a new, 9 cm solitary pulmonary mass in the right lower lobe. After thoracotomy, this lesion was ultimately found to be lymphomatoid granulomatosis, a rare lymphoproliferative disorder. Radiographic evaluations of patients with this disorder characteristically show multiple, bilateral reticulonodular opacities that follow the bronchovascular bundles; however, presentation with a solitary, large pulmonary mass is rare. The present case illustrates the need for complete evaluation of new clinical and radiographic findings in the setting of chronic lung disease.